2014
DOI: 10.1021/am501227y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Reversible Liquefaction and Solidification of Multiazobenzene Sugar-Alcohol Derivatives and Application to Reworkable Adhesives

Abstract: Multiazobenzene compounds, hexakis-O-[4-(phenylazo)phenoxyalkylcarboxyl]-D-mannitols and hexakis-O-[4-(4-hexylphenylazo)phenoxyalkylcarboxyl]-D-mannitols, exhibit photochemically reversible liquefaction and solidification at room temperature. Their photochemical and thermal phase transitions were investigated in detail through thermal analysis, absorption spectroscopy, and dynamic viscoelasticity measurements, and were compared with those of other sugar-alcohol derivatives. Tensile shear strength tests were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
139
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 56 publications
3
139
0
2
Order By: Relevance
“…[33][34][35][36] Introduction of pendant groups at the 2-or 3-position can reduce intermolecular π-π interactions and allow photoisomerization in the bulk state on the time scale of minutes. [28] Recent work has also suggested that lamellar or monolayer azobenzene morphologies facilitate fast photoisomerization, [26,27,37] presumably by providing increased molecular freedom. In our exfoliated monolayer system, rapid photoliquefaction is enabled by the presence of highly disordered and fluidic ODMS surrounding monolayers of crystalline azobenzene.…”
Section: Reversible Photoliquefaction and Photosolidification Of Silomentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36] Introduction of pendant groups at the 2-or 3-position can reduce intermolecular π-π interactions and allow photoisomerization in the bulk state on the time scale of minutes. [28] Recent work has also suggested that lamellar or monolayer azobenzene morphologies facilitate fast photoisomerization, [26,27,37] presumably by providing increased molecular freedom. In our exfoliated monolayer system, rapid photoliquefaction is enabled by the presence of highly disordered and fluidic ODMS surrounding monolayers of crystalline azobenzene.…”
Section: Reversible Photoliquefaction and Photosolidification Of Silomentioning
confidence: 99%
“…[24,25] Furthermore, few examples have demonstrated the photocontrolled switching of liquid and solid phases in azobenzene materials. [26][27][28][29] Given the importance of molecular arrangement in photoresponsive materials, self-assembly strategies that facilitate ordering of functional motifs are prudent. Recently, we reported on the synthesis of a class of well-defined and discrete end-functionalized siloxane oligomers that form highly ordered multidomain nanomaterials with sub-5 nm periodicities.…”
mentioning
confidence: 99%
“…In an application point of view, this phase transition is of importance because this kind of phase transition material can be potentially be used in reusable light adhesives (dismantlable adhesives), photoresists, and other functional materials. Actually, it has been demonstrated that azobenzene-based materials can be used as dismantlable adhesives, that drastic decrease and recovery of the adhesion force were observed by the irradiation with ultraviolet and visible light, respectively [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous layer was separated and extracted with CHCl 3 . The combined CHCl 3 phases were washed with water, dried over MgSO 4 , and concentrated to dryness to afford 2. The yield was 8.34 g (69%).…”
Section: Synthesis Of Four-armed Star-shaped Pba With Azide End Groupsmentioning
confidence: 99%
“…[1][2][3] This strategy is preferable for photoreversible adhesive applications, which enables ON-OFF attachment and detachment of surfaces coated by them without using solvent fractions. 4 Although the IRLNC strategy should, in principle, be applicable for tuning viscoelasticity of materials, only two physical states, i.e., solid and liquid ones are allowed for such small molecules. Therefore, the development of materials exhibiting solvent-free IRLNC with tunable viscoelasticity remains a challenge.…”
mentioning
confidence: 99%